Influences of MJO-induced Tropical Cyclones on the Circulation-Convection Inconsistency for the 2021 South China Sea Summer Monsoon Onset - Chen, Yanying; Jiang, Ning; Ai, Yang; Xu, Kang; Mao, Longjiang (Advances in atmospheric sciences, 2023)
The South China Sea Summer Monsoon (SCSSM) onset is characterized by an apparent seasonal conversion of circulation and convection. Accordingly, various indices have been introduced to identify the SCSSM onset date. However, the onset dates as determined by various indices can be very inconsistent. It not only limits the determination of onset dates but also misleads the assessment of prediction skills. In 2021, the onset time as identified by the circulation criteria was 20 May, which is 12 days earlier than that deduced by also considering the convection criteria. The present study mainly ascribes such circulation-convection inconsistency to the activities of tropical cyclones (TCs) modulated by the Madden-Julian Oscillation (MJO). The convection of TC “Yaas” (2021) acted as an upper-level diabatic heat source to the north of the SCS, facilitating the circulation transition. Afterward, TC “Cho-wan” (2021) over the western Pacific aided the westerlies to persist at lower levels while simultaneously suppressing moist convection over the SCS. Accurate predictions using the ECMWF S2S forecast system were obtained only after the MJO formation. The skillful prediction of the MJO during late spring may provide an opportunity to accurately predict the establishment of the SCSSM several weeks in advance.